Producción y evaluación de proteína unicelular a partir de yuca - Santos Núñez, Jorge; Gómez, G. (International Center for Tropical Agriculture, 1979)
A process for the production of SCP was developed and tested under lab conditions at the U. of Guelph. The microorganism used is the fungus Aspergillus fumigatus I-21A, a mutant that does not produce spores and can grow under very selective conditions at a temp of 45 degrees Celsius and a pH of 3.5. A pilot center was constructed at CIAT to evaluate the technology developed on a lab scale and to produce a sufficient quantity of biomass for the practical evaluation with animal feed, especially swine. A report is given on the most recent results obtained at the pilot plant. Results of various feeding trials with protein biomass, obtained at the pilot plant, indicate that the product has a good nutritional quality, whenever it is adequately supplemented with met. (AS-CIAT)